Display screen functional film and preparation method and application thereof

By coating SiO2 nanoparticles with TiO2 and combining epoxy-containing silane coupling agent and 4,4'-diaminodiphenylsulfone, a display functional film with good light transmittance and strong UV protection performance was prepared, which solved the problem of insufficient UV protection performance in the prior art, and simplified the process and reduced the cost.

CN119667825AActive Publication Date: 2025-03-21TAIHU JINZHANG TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411717355.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-21
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing display functional film still has room for improvement in UV light resistance, and the preparation process is complex, the equipment requirements are high, and the cost is high.

Method used

By coating SiO2 nanoparticles with TiO2, modified SiO2@TiO2 particles are prepared and combined with epoxy group-containing silane coupling agent and 4,4'-diaminodiphenylsulfone to form an efficient functional film coating, coated onto an optical film, and obtain a functional film by heating and drying.

Benefits of technology

It realizes good light transmittance, strong UV light resistance and wear resistance of the functional film, simple process, easy to produce on a large scale, and is suitable for all types of display screens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005157162170000071
    Figure BDA0005157162170000071
  • Figure BDA0005157162170000081
    Figure BDA0005157162170000081
Patent Text Reader

Abstract

The invention discloses a display screen functional film and a preparation method and application thereof, and belongs to the technical field of functional film materials. Comprising the following steps: S1, mixing SiO2 nanoparticles, ethanol, acetonitrile, polyvinylpyrrolidone and deionized water, and carrying out uniform ultrasonic dispersion to obtain a dispersion liquid; slowly dropwise adding tetrabutyl titanate into the dispersion liquid, heating, stirring, washing, drying and annealing to obtain SiO2-coated TiO2 particles; and mixing the SiO2-coated TiO2 particles, a silane coupling agent containing an epoxy group and methanol, heating, stirring, washing and drying to obtain the modified SiO2-coated TiO2 particles. S2, dispersing the modified SiO2 (at) TiO2 particles, 4, 4 '-diaminodiphenyl sulfone and a flatting agent into methyl isobutyl ketone, uniformly mixing, and ultrasonically defoaming to obtain a coating; the coating is uniformly coated on an optical film, and the functional film with good light transmission, ultraviolet light resistance and hydrophobicity is obtained after heating and drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional film materials, and in particular relates to a display screen functional film and a preparation method and application thereof. Background Art

[0002] Functional films for display screens are mainly used in the fields of electronics, packaging materials, industry (including automobiles), aerospace, etc. In display technology, they are used to improve display effects and user experience, such as polarizers, backlight module optical films, etc. With the popularity of electronic consumer products such as smart phones and tablets, the demand for large-screen in-vehicle infotainment is growing. The technology of functional films for display screens is developing in the direction of being thinner, softer and more functional. The functional films have gradually changed from single anti-glare and fingerprint-resistant functions to multifunctional optical films with anti-glare, anti-reflection and fingerprint resistance. At present, display functional films with low reflection function are produced by vacuum coating, which has high requirements for production equipment and production processes. Another method is to add hollow silica particles with low refractive index to the coating to prepare a functional coating to achieve the effect of anti-reflection. However, the high cost and technical barriers of hollow silica particles limit its development.

[0003] The patent application with publication number CN 115895327 A discloses a display screen functional film and its preparation method and application. The functional film adopts flower-shaped silica particles, which have good compatibility with other components of the coating, and also has the advantages of low refractive index and stable physical and chemical properties. The functional film prepared by this silica particles has the characteristics of high light transmittance, anti-reflection, anti-glare, and excellent fingerprint resistance, thereby improving the safety and convenience of vehicle-mounted display screens; however, further improvements can be made in terms of functionalization, such as improving antibacterial, UV / blue light protection, etc. Summary of the invention

[0004] The object of the present invention is to provide a display screen functional film and a preparation method and application thereof, so as to improve the anti-ultraviolet light performance of the display screen functional film.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a functional film of a display screen comprises the following steps:

[0007] S1. Mix SiO2 nanoparticles, ethanol, acetonitrile, polyvinyl pyrrolidone and deionized water, and disperse them uniformly by ultrasonication to obtain a dispersion; slowly drop tetrabutyl titanate into the dispersion, heat and stir, wash and dry, and anneal to obtain SiO2@TiO2 particles; mix SiO2@TiO2 particles, an epoxy-containing silane coupling agent and methanol, heat and stir, and wash and dry to obtain modified SiO2@TiO2 particles;

[0008] S2. Disperse the modified SiO2@TiO2 particles, 4,4'-diaminodiphenyl sulfone and leveling agent in methyl isobutyl ketone, mix well, and perform ultrasonic degassing to obtain a coating; apply the coating evenly on the optical film, and obtain a functional film after heating and drying.

[0009] Furthermore, the dosage ratio of the SiO2 nanoparticles, anhydrous ethanol, acetonitrile, polyvinyl pyrrolidone, deionized water and tetrabutyl titanate is (5-7.5) g: (750-900) mL: (100-200) mL: (0.5-1) g: (400-500) mL: (30-50) mL.

[0010] Furthermore, the heating and stirring is stirring at 55-65° C. for 12-14 hours; and the annealing is annealing at 500-600° C. for 2-3 hours.

[0011] Furthermore, the usage ratio of the SiO2@TiO2 particles, the epoxy-containing silane coupling agent and methanol is (5-7.5) g: (0.8-1) g: (250-350) mL.

[0012] Furthermore, the epoxy-containing silane coupling agent is one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane and 3-glycidyloxypropyltriethoxysilane.

[0013] Furthermore, the modified SiO2@TiO2, 4,4'-diaminodiphenyl sulfone, and leveling agent dispersed in methyl isobutyl ketone are used in a ratio of (3-6) g: (0.3-0.5) g: (0.01-0.03) g: (25-35) mL.

[0014] Furthermore, the coating thickness is 6 to 10 μm, and the temperature drying is 155 to 175° C. for 6 to 8 hours.

[0015] Furthermore, a display screen functional film is prepared by the above-mentioned display screen functional film preparation method.

[0016] Furthermore, the display screen functional film is used in a display screen.

[0017] Beneficial effects of the present invention:

[0018] (1) The functional film for a display screen provided by the present invention has good light transmittance and UV protection performance, a simple preparation process, is easy for large-scale production, and can be widely used in various types of display screens.

[0019] (2) The modified SiO2@TiO2 particles used in the present invention coat TiO2 in the outer layer of SiO2, thereby improving the compatibility between TiO2 and SiO2 materials and preventing spontaneous agglomeration of particles. The addition of TiO2 can also absorb and reflect ultraviolet rays, and has a strong barrier ability to ultraviolet rays.

[0020] (3) The epoxy-containing silane coupling agent used in the present invention improves the dispersibility between SiO2@TiO2 particles. At the same time, the epoxy group of the coupling agent and the amino group of 4,4'-diaminodiphenyl sulfone form a covalent bond, thereby improving the mechanical properties of the material. On the other hand, the phenyl group contained in 4,4'-diaminodiphenyl sulfone improves the hydrophobicity and mechanical strength of the material, thereby improving the wear resistance of the functional film. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] This embodiment provides a display screen functional film, which is prepared by the following steps:

[0024] S1. Mix 6 g SiO2 nanoparticles, 800 mL ethanol, 150 mL acetonitrile, 0.6 g polyvinyl pyrrolidone and 450 mL deionized water, and disperse them uniformly by ultrasonication to obtain a dispersion; slowly add 45 mL tetrabutyl titanate to the dispersion, stir at 65 °C for 12 h, wash and dry, and anneal at 600 °C for 2 h to obtain SiO2@TiO2 particles; mix 6 g SiO2@TiO2 particles, 1 g γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 300 mL methanol, heat and stir, wash and dry to obtain modified SiO2@TiO2 particles.

[0025] S2. Disperse 5 g of modified SiO2@TiO2 particles, 0.4 g of 4,4'-diaminodiphenyl sulfone, and 0.02 g of a leveling agent in 30 mL of methyl isobutyl ketone, mix well, and perform ultrasonic degassing to obtain a coating; evenly apply the coating to an optical film with a coating thickness of 8 μm, and dry at 175° C. for 6 h to obtain the functional film.

[0026] The prepared functional film is applied to a display screen.

[0027] Example 2

[0028] The present embodiment is different from the embodiment 1 in that the “6 g SiO2 nanoparticles” and “45 mL tetrabutyl titanate” in S1 are changed to “5 g SiO2 nanoparticles” and “50 mL tetrabutyl titanate”.

[0029] The remaining raw materials and preparation process remain the same as in Example 1.

[0030] Example 3

[0031] The present embodiment is different from the embodiment 1 in that the “6 g SiO2 nanoparticles” and “45 mL tetrabutyl titanate” in S1 are changed to “7 g SiO2 nanoparticles” and “30 mL tetrabutyl titanate”.

[0032] The remaining raw materials and preparation process remain the same as in Example 1.

[0033] Example 4

[0034] Compared with Example 1, the present embodiment is different in that "6 g SiO2@TiO2 particles, 1 g γ-(2,3-epoxypropoxy)propyltrimethoxysilane" in S1 is changed to "5 g SiO2@TiO2 particles, 1 g γ-(2,3-epoxypropoxy)propyltrimethoxysilane".

[0035] The remaining raw materials and preparation process remain the same as in Example 1.

[0036] Example 5

[0037] Compared with Example 1, the difference between this example and this example is that "6g SiO2@TiO2 particles, 1g γ-(2,3-epoxypropoxy)propyltrimethoxysilane" in S1 is changed to "7g SiO2@TiO2 particles, 0.8g γ-(2,3-epoxypropoxy)propyltrimethoxysilane".

[0038] The remaining raw materials and preparation process remain the same as in Example 1.

[0039] Example 6

[0040] The present embodiment is different from the embodiment 1 in that the "γ-(2,3-epoxypropoxy)propyltrimethoxysilane" in S1 is replaced with "trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane".

[0041] The remaining raw materials and preparation process remain the same as in Example 1.

[0042] Example 7

[0043] Compared with Example 1, the present embodiment is different in that "5 g modified SiO2@TiO2 particles, 0.4 g 4,4'-diaminodiphenyl sulfone, 0.02 g leveling agent" in S2 is changed to "4 g modified SiO2@TiO2 particles, 0.5 g 4,4'-diaminodiphenyl sulfone, 0.03 g leveling agent".

[0044] The remaining raw materials and preparation process remain the same as in Example 1.

[0045] Example 8

[0046] The present embodiment differs from the embodiment 1 in that “the coating thickness is 8 μm” is changed to “the coating thickness is 6 μm”.

[0047] The remaining raw materials and preparation process remain the same as in Example 1.

[0048] Example 9

[0049] The present embodiment differs from the embodiment 1 in that “the coating thickness is 8 μm” is changed to “the coating thickness is 10 μm”.

[0050] The remaining raw materials and preparation process remain the same as in Example 1.

[0051] Comparative Example 1

[0052] Compared with Example 1, the difference between this comparative example and Example 1 is that S1 is not coated with TiO2. The specific implementation steps of S1 are as follows:

[0053] S1. Mix 6 g of SiO2 nanoparticles, 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 300 mL of methanol, heat and stir, wash and dry to obtain modified SiO2 particles.

[0054] The remaining raw materials and preparation process remain the same as in Example 1.

[0055] Comparative Example 2

[0056] Compared with Example 1, the difference between this comparative example is that SiO2 and TiO2 in S1 are directly mixed, and the specific implementation steps of S1 are:

[0057] S1. Mix 6 g SiO2 nanoparticles, 800 mL ethanol, 150 mL acetonitrile, 0.6 g polyvinyl pyrrolidone and 450 mL deionized water, and disperse them uniformly by ultrasonication to obtain a dispersion; add 2 g TiO2 nanoparticles to the dispersion, stir at 65 °C for 12 h, wash and dry, and anneal at 600 °C for 2 h to obtain SiO2 / TiO2 particles; mix 6 g SiO2 / TiO2 particles, 1 g γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 300 mL methanol, heat and stir, wash and dry to obtain modified SiO2 / TiO2 particles.

[0058] The remaining raw materials and preparation process remain the same as in Example 1.

[0059] Comparative Example 3

[0060] Compared with Example 1, the difference between this comparative example is that "γ-(2,3-epoxypropoxy)propyltrimethoxysilane" is replaced with "silane coupling agent KH550"

[0061] The remaining raw materials and preparation process remain the same as in Example 1.

[0062] Comparative Example 4

[0063] The difference between this comparative example and Example 1 is that 4,4'-diaminodiphenyl sulfone is not added to S2.

[0064] The remaining raw materials and preparation process remain the same as in Example 1.

[0065] Comparative Example 5

[0066] Compared with Example 1, the difference between this comparative example is that no silane coupling agent and 4,4'-diaminodiphenyl sulfone are added at the same time, and the specific implementation steps are as follows:

[0067] S1. 6 g SiO2 nanoparticles, 800 mL ethanol, 150 mL acetonitrile, 0.6 g polyvinyl pyrrolidone and 450 mL deionized water were mixed and uniformly dispersed by ultrasonication to obtain a dispersion; 45 mL tetrabutyl titanate was slowly added dropwise to the dispersion, stirred at 65°C for 12 h, washed and dried, and annealed at 600°C for 2 h to obtain SiO2@TiO2 particles;

[0068] S2. Disperse 5 g of SiO2@TiO2 particles and 0.02 g of a leveling agent in 30 mL of methyl isobutyl ketone, mix well, and perform ultrasonic degassing to obtain a coating; apply the coating evenly on the optical film to a thickness of 8 μm, and dry at 175° C. for 6 h to obtain the functional film.

[0069] The remaining raw materials and preparation process remain the same as in Example 1.

[0070] The performance tests were performed on the functional films prepared in Examples 1 to 9 and Comparative Examples 1 to 5:

[0071] The transmittance of the functional film in the ultraviolet and visible bands was tested using a UV-visible spectrophotometer with a wavelength range of 200 to 800 nm, and the haze of the functional film was tested using a color analyzer;

[0072] A contact angle meter was used to test to ensure that the surface of the functional membrane was clean and dust-free. Distilled water was used to ensure its purity and consistency. The functional membrane was placed flat on the sample table to ensure that the coating surface was flat and free of bubbles. 1 μL of distilled water was added using a microsyringe. Immediately after adding the distilled water, a high-speed camera was used to capture the image and measure the contact angle.

[0073] The wear tester was used for testing. The total load on the functional film was 1000g. The friction material was steel wool. The reciprocating friction frequency was 120 times / min. The friction area was about 40mm×40mm. The contact angle was measured again.

[0074] The results are shown in Table 1:

[0075] Table 1

[0076]

[0077]

[0078] It can be seen from Table 1 that the difference between Examples 2 to 7 and Example 1 is only the change in the raw material content and ratio within a reasonable range. From the results, the prepared functional films have good UV protection, transparency and hydrophobicity. The difference between Examples 8 to 9 and Example 1 is the change in coating thickness. The results show that too thin a coating thickness will affect the performance of the functional film, and too thick a coating thickness will also lead to a decrease in coating performance and an increase in cost.

[0079] Comparison of Examples 1 to 2 and 5 with Example 1 aims to illustrate the influence of whether or not TiO2 is added and the way of adding it on the functional film. The results show that TiO2 coated on the outer layer of SiO2 not only has a strong UV blocking ability, but also improves the compatibility between SiO2 and the material, and prevents spontaneous agglomeration of particles. Comparison of Examples 3 to 5 with Example 1, because the epoxy group of the coupling agent and the amino group of 4,4'-diaminodiphenyl sulfone form a covalent bond, the results show that it still has good hydrophobicity after being rubbed with steel wool, thereby improving the wear resistance of the functional film.

[0080] In summary, the present invention provides a display screen functional film and a preparation method thereof, which are applied to display screens and have good light transmittance, UV protection and hydrophobicity, and have good application prospects in the field of various display screen functional films.

[0081] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a functional film for a display screen, characterized in that: The following steps are involved: S1. Mix SiO2 nanoparticles, ethanol, acetonitrile, polyvinyl pyrrolidone and deionized water, and disperse them uniformly by ultrasonication to obtain a dispersion; slowly drop tetrabutyl titanate into the dispersion, heat and stir, wash and dry, and anneal to obtain SiO2@TiO2 particles; mix SiO2@TiO2 particles, an epoxy-containing silane coupling agent and methanol, heat and stir, and wash and dry to obtain modified SiO2@TiO2 particles; S2. Disperse the modified SiO2@TiO2 particles, 4,4'-diaminodiphenyl sulfone and leveling agent in methyl isobutyl ketone, mix well, and perform ultrasonic degassing to obtain a coating; apply the coating evenly on the optical film, and obtain a functional film after heating and drying.

2. The method for preparing a functional film for a display screen according to claim 1, characterized in that: The dosage ratio of the SiO2 nanoparticles, anhydrous ethanol, acetonitrile, polyvinyl pyrrolidone, deionized water and tetrabutyl titanate is (5-7.5) g: (750-900) mL: (100-200) mL: (0.5-1) g: (400-500) mL: (30-50) mL.

3. The method for preparing a display screen functional film according to claim 1, characterized in that: The heating stirring is stirring at 55-65° C. for 12-14 hours; and the annealing is annealing at 500-600° C. for 2-3 hours.

4. The method for preparing a functional film for a display screen according to claim 1, characterized in that: The usage ratio of the SiO2@TiO2 particles, the epoxy-containing silane coupling agent and methanol is (5-7.5) g: (0.8-1) g: (250-350) mL.

5. The method for preparing a display screen functional film according to claim 1, characterized in that: The epoxy-containing silane coupling agent is one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane and 3-glycidyloxypropyltriethoxysilane.

6. The method for preparing a display screen functional film according to claim 1, characterized in that: The modified SiO2@TiO2, 4,4'-diaminodiphenyl sulfone and leveling agent are dispersed in methyl isobutyl ketone in a dosage ratio of (3-6) g: (0.3-0.5) g: (0.01-0.03) g: (25-35) mL.

7. The method for preparing a functional film for a display screen according to claim 1, characterized in that: The coating thickness is 6-10 μm; the temperature drying is 155-175° C. for 6-8 hours.

8. A display screen functional film, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the display screen functional film according to claim 8 in a display screen.

Citation Information

Patent Citations

  • Display screen functional film and preparation method and application thereof

    CN115895327A

  • Preparation method of titanium dioxide-silicon dioxide-epoxy resin composite super-hydrophobic coating

    CN102702931A

  • Method for preparing super-hydrophobicity surfaces

    CN102863154A

  • Preparation method for core-shell TiO2-SiO2 microsphere self-assembled structural color film

    CN106423000A

  • Ultraviolet-proof titanium dioxide-based automobile coating liquid and preparation method thereof

    CN118325413A